Inside Cover: Coherent Enantiomer‐Selective Population Enrichment Using Tailored Microwave Fields (Angew. Chem. Int. Ed. 41/2017). Issue 41 (5th September 2017) - Pérez, Cristóbal; Steber, Amanda L.; Domingos, Sérgio R.; Krin, Anna; Schmitz, David; Schnell, Melanie
Abstract : Population transfer in chiral molecules is reported as a means to achieve enantiomeric enrichment by C. Pérez, M. Schnell et al. in their Communication on page 12512 ff. Enrichment is achieved by using microwave fields. The Penrose stairs represent the molecular rotational states that are simultaneously excited by three microwave pulses. This excitation leads to significant population enrichment of one enantiomer in a particular rotational level, which is exemplified by the black and red spheres.